2020
DOI: 10.1007/s10633-020-09794-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the orientation-specific pattern-onset visual evoked potentials in children with bilateral refractive amblyopia and non-amblyopic controls

Abstract: Characterising the orientation-specific pattern-onset visual evoked potentials in children with bilateral refractive amblyopia and non-amblyopic controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…Besides, the horizontal effect was only observed in children (3-7 years old) in Yap's study, and the meridional disparity was observed in subjects of older age range (7-26 years old) in our study. According to recent studies (Yap et al, 2019(Yap et al, , 2020bYap and Boon, 2020), the horizontal effect is an indicator of normality. It is important to separate the meridianspecific deficit from the normal physiological phenomenon (i.e., horizontal effect), thus future study could include newly diagnosed amblyopes and meridional amblyopes with other types of regular astigmatism to further clarify it.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the horizontal effect was only observed in children (3-7 years old) in Yap's study, and the meridional disparity was observed in subjects of older age range (7-26 years old) in our study. According to recent studies (Yap et al, 2019(Yap et al, , 2020bYap and Boon, 2020), the horizontal effect is an indicator of normality. It is important to separate the meridianspecific deficit from the normal physiological phenomenon (i.e., horizontal effect), thus future study could include newly diagnosed amblyopes and meridional amblyopes with other types of regular astigmatism to further clarify it.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, changes in the primary and visual cerebral cortex were found in children with refractive amblyopia and in the retina [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%